2003
DOI: 10.1590/s0103-64402003000300005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a non-rinse conditioner on the enamel of primary teeth

Abstract: The aim of this in vitro study was to evaluate by scanning electron microscopy the morphological aspects of the enamel of primary teeth after etching with 36% phosphoric acid or a non-rinse conditioner. Ten naturally exfoliated anterior primary teeth were selected. The samples were subjected to prophylaxis with pumice paste and water using a low-speed hand piece. Etching was done on the buccal surface. Specimens were divided into 2 groups: G1 (n=10): etching with 36% phosphoric acid gel - Conditioner 36 (Dents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
(5 reference statements)
1
3
0
5
Order By: Relevance
“…They observed that the thicker layer of aprismatic enamel in the primary tooth influenced the conditioning etching pattern, which was discrete in the case of self-etching and formed resin tags. Similar findings were observed by Fava et al (2003). These previous observations help explain why the BS of OptiBond All-in-One (which also showed a relationship between BS and micromorphology) was lower than that of OptiBond FL.…”
Section: Discussionsupporting
confidence: 86%
“…They observed that the thicker layer of aprismatic enamel in the primary tooth influenced the conditioning etching pattern, which was discrete in the case of self-etching and formed resin tags. Similar findings were observed by Fava et al (2003). These previous observations help explain why the BS of OptiBond All-in-One (which also showed a relationship between BS and micromorphology) was lower than that of OptiBond FL.…”
Section: Discussionsupporting
confidence: 86%
“…A comparação dos resultados obtidos com os sistemas adesivos autocondicionantes empregados no presente estudo, com outros na literatura, tornou-se inviável devido à escassez de trabalhos conduzidos em dentes decíduos. Outros estudos, também realizados sobre o esmalte de dentes decíduos (ainda que com outros adesivos autocondicionantes, com outras formulações), concordam que estes são menos eficientes do que o ácido fosfórico para promover a formação de uma superfície micro-retentiva (FAVA et al, 2003;CRUZ et al, 2005). Deve-se ressaltar que ambos os estudos foram realizados em superfície de esmalte íntegro, não havendo a observação sobre o esmalte desgastado.…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified
“…Têm sido controversos os relatos sobre as avaliações destes adesivos em esmalte e dentina. Há estudos que demonstram que alguns sistemas adesivos autocondicionantes têm menor habilidade de condicionamento devido ao pH ser relativamente mais básico, se comparado ao ácido fosfórico, tanto em esmalte intacto como desgastado, seja em dentes permanentes (DE MUNCK et al, 2003;FRITZ, 1996;HASHIMOTO et al, 2003;KANEMURA;TAGAMI, 1999;PERDIGÃO et al, 1997) ou decíduos (DARONCH et al, 2003FAVA et al, 2003). Por outro lado, autores afirmam que o condicionamento p roduzido é suficiente para criar união, forte e estável, quando aplicados em esmalte permanente desgastado LOS;TRIOLO, 1995;BRESCHI et al, 2003;KAADEN et al, 2002;KANEMURA;TAGAMI, 1999;KIREMITÇI;YALÇIN;GÖKALP, 2004 (TAY et al, 2004).…”
Section: Adesão Ao Esmalteunclassified
“…Haveria diferenças em relação à adesão? Poucas pesquisas relacionadas a este assunto têm sido realizadas com dentes decíduos (AGOSTINI; POWERS, 2001;DARONCH et al, 2003;FAVA et al, 2003;RAMIRES-ROMITO et al, 2004).…”
Section: Adesão Ao Esmalteunclassified
See 1 more Smart Citation